Enhancing Cognitive Learning: A Comparative Analysis of E-Learning Media Tailored to Different Learning Styles - Atiek Winarti; Almubarak; Titi Sundari; Bambang Sumardjoko; Zakhele Nzuza (Universitas Muhammadiyah Surakarta, 2024)
This study aims to analyze the effectiveness of e-learning media based on learning style in the form of e-posters, podcasts, and interactive videos on students' cognitive learning outcomes. This type of research is quantitative research. This study used a sample of 32 grade X PMIA 1 SMA Negeri 3 Banjarmasin students. This research uses Google Classroom as a platform for learning activities. Learning media in the form of e-posters, podcasts, interactive videos, and student learning outcomes can be downloaded and uploaded on Google Classroom. The research instrument used is a learning style questionnaire containing 30 statements. Data analysis in this study used a normality test, and Wilcoxon signed rank test. The cognitive learning outcomes of students with visual, auditory, and kinesthetic learning styles were 90.66%, 93.33%, and 87.33%, respectively, with N-gain values of 0.75, 0.80, and 0.71. Based on data analysis, the results of this study show that e-learning media based on learning style is efficacious in improving the cognitive learning outcomes of students with visual, auditory, and kinesthetic learning styles. This learning style-based e-learning media can be applied to other chemical materials or subjects. The study employed-N-gain values to analyst the learning outcomes of the students. The - N gain values for students with visual, auditory and kinesthetic learning styles were 0.75, 0,80 and 0.71 respectively. Overall, the data suggests that the learning outcomes of the students were quite positive and that the use of various learning media and Google Classroom as a platform can be effective in enhancing students learning outcomes.